2022
DOI: 10.1088/1742-6596/2204/1/012026
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the deterioration of lead artifacts. A case study on piano keys and their degradation products

Abstract: Among musical instruments, Piano is one of the most important and fascinating ones of all years for its completeness from a harmonic point of view and for the importance it has held in the world of classical music of the great composers. In this context, old pianos can be considered as real pieces of art thus their conservation is included in the preservation of cultural heritage. The aim of this work is to study the deterioration of some lead weights of piano keys from an important, luxury and one of the best… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Recently, we analysed for the first time the degradation compounds of one LW sample from a Steinway & sons piano (Faggiano et al 2022 ). These preliminary results suggested that the lead of LW degraded into hydrocerussite.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we analysed for the first time the degradation compounds of one LW sample from a Steinway & sons piano (Faggiano et al 2022 ). These preliminary results suggested that the lead of LW degraded into hydrocerussite.…”
Section: Introductionmentioning
confidence: 99%